Study on coupling coordination of the human settlement environment and tourism industry in the yellow river basin - Yu, Xiao; Chen, Hanxue (Frontiers in Environmental Science, 2022)
The coordinated development of the human settlement environment and the tourism industry provides vital support for high-quality sustainable development in the region, but the related research is relatively insufficient. Based on the panel data from 2010 to 2019, this study takes the Yellow Basin as the research object, using comprehensive evaluation, coupling degree, and coupling coordination models. The study aims to comprehensively measure the development level of the human settlement environment and tourism industry in nine provinces of the Yellow River Basin and analyzes the spatio-temporal differentiation characteristics of the coupling coordination between the human settlement environment and tourism industry in the Yellow River Basin. The results demonstrate an interactive coupling relationship between the human settlement environment and the tourism industry. We observe an upward fluctuation in the development level of the two systems in the Yellow River Basin and converging development trends between the two; however, the tourism industry in the region is far behind in driving the construction of the human settlement environment. Regarding the spatial and temporal evolution of the coupling coordination of the two systems, in the time dimension, the coupling degree of the nine provinces in the Yellow River Basin was relatively stable from 2010 to 2019 and maintained a high level. The coupling coordination degree was on the rise, evolving from near-disorder to elementary coordination. The two systems in the Basin still showed a pattern of “high coupling-low coordination.” Nevertheless, in the spatial dimension, the coupling and coupling coordination degrees of the two systems in the Yellow River Basin showed an unbalanced development pattern of “high in the southeast and low in the northwest.” The regions with a low coordination level demonstrated that the development of the tourism industry lags behind in the construction of the human settlement environment. Findings in this study provide references for increasing the resonance between the human settlement environment and the tourism industry and promoting the overall coordinated, balanced and sustainable development of the Yellow River Basin.